If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying cos + 2sec = -3 Reorder the terms: 2ces + cos = -3 Solving 2ces + cos = -3 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Reorder the terms: 3 + 2ces + cos = -3 + 3 Combine like terms: -3 + 3 = 0 3 + 2ces + cos = 0 The solution to this equation could not be determined.
| -16=2(1-5x)+4 | | x+3.5=8.5-9x | | 10x-5(x-2)=30 | | 7-4x-3x-5=6x+1+2x-3 | | =(4x-3)(2x+7)-(4x-3)(6-x) | | 3(a+b)+2(a-b)= | | 0.1x+0.25x=20.65 | | -3=153 | | 2v-26=-9(v+9) | | 9x-10=2x+6 | | 6(2.5+3x)-13x=8x-24 | | 16n-6-9n=43-2n+5 | | -6(2-4n)+5=161 | | y(y+5)+2(y-3)= | | 5(3x-4)=32+2x | | 336=6(-6x+8) | | 34-3x=6x+7 | | 0.66x-10=0.5x-8 | | 12t=-123 | | 364=-5(8n-8)+4 | | 2f(x)=4x-2 | | 2x-b=3 | | 0.2=10 | | 4r-4+8=-16 | | 2(x-6)-4x=-14 | | 4+3b+1=8 | | 84=2x+2x^2 | | 12=1-6n-5n | | 72=(a*10)+(a*2a) | | 5(t-3)-3(2-t)= | | 15x-7x=8x | | 1.3+5(x-0.1)=-1.2-3x |